A critical analysis of the recent Interstate Commerce Act - Nevines, Clarence G. (My University, 1907)
Introduction: When in 1787 the drafters of the Constitution for the original thirteen states inserted a provision declaring that all interstate commerce should be under the control of the federal government, they little dreamed of the immense significance that was attached to these few words. At that time there was little commerce carried on between the different states and, as for the condition today there is no necessity of taking the time to expound to the American public, the vital connection that our Interstate Commerce has with our existence as one of the great nations. The first law passed under this provision of the constitution was not until 1887, and it was on that related to interstate railroads only. This act had some rules and principles for the controlling of interstate railroads and provided for the establishment of a commission of five members who were to be appointed by the President. It was to become the duty of this commission to apply and enforce the law. Each commissioner was to hold office for six years and was to draw a salary of $7,500 per annum. One of the most renowned constitutional scholars in the whole country, Hon. Thomas M. Cooley, was the first president of the commission. They were to hold sessions all over the United States as the occasion required, but the larger number of its sessions were to be held in Washington, D. C. The commission was…
Citation: Nevines, Clarence G. A critical analysis of the recent Interstate Commerce Act. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Interstate Commerce Act; Commerce in the United States; Restrictions on Trade; Theses